Thermoelastic Properties of Liquid Fe‐Rich Alloys Under Martian Core Conditions. Issue 6 (16th March 2023) - Huang, D.; Li, Y.; Khan, A.; Sossi, P.; Giardini, D.; Murakami, M.
Abstract: Seismic measurements made on Mars indicate that the liquid iron‐nickel core is rich in light elements; however, the effects of these light components on the elasticity of Mars' core remain poorly constrained. Here, we calculate elastic properties of various liquid Fe‐X (X = Ni, S, C, O and H) mixtures using ab initio molecular dynamics simulations. We find that, at martian core conditions, the addition of S and O most effectively decreases the density of liquid iron, followed by C and H, while Ni has a minimal effect. As for compressional sound velocity (Vp), C increases Vp of liquid Fe throughout Mars' core, while both S and O reduce Vp, the intensity of which diminishes with increasing pressure. Assuming a martian core made of a binary mixture, the seismically‐inferred density would require the presence of at least 30 wt% S. Plain Language Summary: Planetary structure and chemical constitution is a product of the material from which it formed. As a planet assembles material and continues to grow, it undergoes melting, enabling heavy elements like Fe and Ni to settle toward the center of the planet to form a core. During core formation, liquid metals can incorporate light elements (LEs) such as S, C, O and H that lower the density of the core relative to pure Fe. The amounts of these LEs can be inferred from geophysical measurements such as seismology, an approach used to deduce the composition of Earth's core. Similar seismic measurements have been obtained for Mars with the InSight mission, which have allowed us to place limits on the mean density of Mars' core and its chemical make‐up. Relative to Earth's core, Mars' core is significantly less dense, requiring the presence of considerable amounts of LEs. We performed simulations based on first principles to determine the elastic properties of various Fe‐Ni‐rich‐LE mixtures that can be compared with those obtained from for example, InSight to place further constraints on its core composition, but can also be used for other planets such as Mercury and mid‐sized exoplanets. Key Points: Unlike S, the densities of Ni, C, O and H mix ideally with liquid Fe at Mars' core conditions Of the light elements (LEs), C and S have the largest effects on the bulk sound velocity of liquid Fe To match the density of Mars' core, any Fe‐X binary requires a substantial amount of LE (e.g., >30 wt% S)